Recent Advances in Electromagnetic Devices (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue, titled “Recent Advances in Electromagnetic Devices”, explores the latest developments in the field of electromagnetic technology, focusing on innovations in design, materials, and applications. A central theme of this Special Issue is the optimization of device efficiency, miniaturization, and integration with other technologies. Examples of key advancements within this field include the following:Metamaterials, which enable novel properties and functions that are not found in natural materials, leading to breakthroughs in antenna design, cloaking, and electromagnetic shielding.Wireless power transfer, which allows for efficient energy transmission over short and long distances, with applications in consumer electronics and electric vehicles. Electromagnetic actuators and sensors, which have the potential to improve robotic systems, medical devices, and aerospace engineering. Optical devices and photonic devices such as lenses, mirrors, microscopes, fiber optics, imaging, sensing, lasers, solar energy harvesting, photodetectors, and biomedical research apparatus.